2014
DOI: 10.1186/1742-4690-11-s1-o46
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from HTLV-1 infected cells contain the viral protein Tax

Abstract: Human T-lymphotropic virus type 1 (HTLV-1) is the causative agent of adult T-cell leukemia. The HTLV-1 transactivator protein Tax has been identified as a critical component in the proliferation and transformation of human primary T-cells. This 40 kDa phosphoprotein not only manipulates chromatin remodeling within the host, but also subverts host cell DNA damage response mechanisms, cell cycle progression, and apoptosis. Here we utilized a combination of filtration and ultracentrifugation methods to enrich for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Though there are significant data available on the role of EVs in pulmonary diseases, the involvement of EVs in HTLV-1-associated alveolitis and bronchiectasis still remains unexplored. It is possible that EVs from HTLV-1-infected cells carrying Tax and ICAM-1 [ 57 , 82 , 197 ] may be a participant in the increased inflammation observed in these patients. A further detailed study is warranted to explore how EVs can contribute in the pathophysiology of pulmonary disease associated with HTLV-1 infection.…”
Section: Evs In Htlv-1-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Though there are significant data available on the role of EVs in pulmonary diseases, the involvement of EVs in HTLV-1-associated alveolitis and bronchiectasis still remains unexplored. It is possible that EVs from HTLV-1-infected cells carrying Tax and ICAM-1 [ 57 , 82 , 197 ] may be a participant in the increased inflammation observed in these patients. A further detailed study is warranted to explore how EVs can contribute in the pathophysiology of pulmonary disease associated with HTLV-1 infection.…”
Section: Evs In Htlv-1-related Diseasesmentioning
confidence: 99%
“…Moreover, in the case of virally induced cancers such ATLL, tumor-derived EVs carry viral proteins can possibly upregulate host proteins and exacerbate the course of the disease. EVs may potentially play a major role in HTLV-1 induced cancers as they often contain viral proteins and RNAs that can influence cell cycle in the recipient cells [ 88 , 197 ]. Removal of the tumor-derived EVs from the cell-cell communication environment might provide therapeutic benefits to patients.…”
Section: Treatments Used To Modulate Ev Biogenesis Release and Umentioning
confidence: 99%
“…Numerous studies have demonstrated that exosomes participate in cell-to-cell communication and the transfer of biologically active molecules [21,26]. Recent studies have shown that exosomes released from cells infected with viruses, such as human immunodeficiency virus, human T-cell lymphotropic virus, HCV, Epstein-Barr virus (EBV), herpesvirus, or human papillomavirus, harbor and deliver many biologically active molecules, including viral and cellular RNAs and proteins, to neighboring cells, helping to establish productive infections [22,23,31,32,33,34]. On the other hand, additional studies have demonstrated that exosomes mediate intercellular transmission of antiviral molecules (e.g., type I IFNs, NKG2D ligands, and miRNA-29) and limit viral infection [29,30,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another human retrovirus, the human T-lymphotropic virus 1 (HTLV-1), also appears to export viral components via the exosomal transport systems. Exosomes released from HTLV-1-infected cells contain not only viral mRNA transcripts, such as those for Tax, HBZ, and Env, but also the biologically active trans-activator protein, Tax [86,87]. Moreover, HTLV-1 Tax protein has been demonstrated in exosomes isolated from cerebrospinal fluid of patients with HTLV-1-associated myelopathy/tropical spastic paraparesis, suggesting that HTLV-1 may modulate its microenvironment by selective secretion of specific viral cargo [88].…”
Section: Viral Signatures In Exosomesmentioning
confidence: 99%